0306 Parental occupational exposure to ionising radiation and selected birth defects in the US. (23rd June 2014) - Lim, H; Agopian, AJ; Whitehead, LW; Beasley, CW; Langlois, PH; Emery, RJ; Waller, DK
Abstract : Objectives: Results of previous studies of occupational exposure to ionising radiation (IR) and birth defects are inconsistent. Our objective was to assess the association between maternal and paternal occupational exposure to ionising radiation (IR) and birth defects using a larger sample than previous studies. Method: We studied 27 809 case mothers and 10 200 control mothers who participated in the National Birth Defects Prevention Study (NBDPS), giving birth between 1997 and 2009. Our exposure assessment was based on a textual analysis of the mother's description of her occupation, workplace and job activities (and those of the infant's father) during the three months before and the three months after the estimated date of conception. Logistic regression was used to examine crude and adjusted odds ratios for the association between possible maternal and paternal occupational exposures to IR and 45 birth defects. We assessed the possibility of confounding from pre-pregnancy diabetes and body mass index, smoking, use of supplements containing folic acid, use of alcohol, use of illicit drugs, pregnancy intention, study location and demographic variables. Results: We excluded 17 mothers with a history of cancer, and 12 568 mothers who were unemployed, homemakers or students during the periconceptional period. Overall, 3% of the mothers and 2% of the fathers were exposed to IR. The remainder of our results are underway and will be presented at the meeting. Conclusions: Our results will be interpreted taking account of multiple statistical comparisons and the possibility of recall bias.